Peningkatan Minat dan Kemampuan Membaca untuk Menambah Pengetahuan dan Hasil Belajar Peserta Didik Kelas XI Menggunakan Metode Quantum Reading di SMK Negeri 1 Sogae’adu - Harefa, Faona’atulo; Halawa, Alexander Julvin; Gulo, Necis Putra; Bu’ulolo, Yustina; Waruwu, Niberkati; Hulu, Pasrah Eli (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to increase the reading interest of grade XI students using the quantum reading method at SMK Negeri 1 Sogae'adu. This type of research is action research. This research uses qualitative data analysis techniques to describe and explain the data produced in the form of information. The subjects of this study were students from class XI in students from class XI at SMK Negeri 1 Sogae'adu, but researchers only made observations in one class, namely in the TKR (Light Vehicle Engineering) department class which amounted to 32 people. The results of the study in the first cycle were 68.30 with a percentage of classical learning completeness of 68.75%. This is because 10 people out of 32 students have not reached learning completion. In cycle II the average score increased to 75.94 with the percentage of classical learning completeness reaching 85.89%. The use of the Quantum Reading Method to improve reading skills in students is effective in improving learning outcomes and student activity in reading